Mathematical Literacy In Solving Hots-Based Problems On Spldv Material In Terms of Cognitive Style - Lively, Wanodya Kirana Intan; Machromah, Isnaeni Umi (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
The concept of mathematical aptitude pertains to an individual's capacity to articulate, elucidate, and employ mathematical principles in everyday scenarios. This investigation stemmed from concerns surrounding substandard levels of mathematical literacy, potentially stemming from students' inability to meet established benchmarks. The primary objective of this inquiry was to evaluate students' mathematical acumen in tackling HOTS-based challenges linked to SPLDV materials, while considering their cognitive inclinations. Employing a qualitative framework with a descriptive approach, the study centered on four eighth-grade students from SMP Negeri 3 Colomadu, comprising two individuals exhibiting a field-dependent cognitive style and two with a field-independent cognitive orientation. Data on the participants' mathematical proficiencies were gathered through a combination of assessment tools and interviews, complemented by a cognitive style questionnaire. The validity of the data was fortified through triangulation methodologies. Analysis ensued through three distinct phases: data reduction, presentation, and synthesis. The results showed that students with Field Dependent cognitive style type only fulfill one indicator of mathematical literacy, namely communication. While students with cognitive style type Field Independent able to meet all indicators of mathematical literacy well include communication, mathematization, representation, reasoning and argumentation, designing strategies to solve problems, as well as the use of operations, symbols, formal, and technical.